A combined bioprocess based on solid-state fermentation for dark fermentative hydrogen production from food waste. (20th January 2016) - Han, Wei; Ye, Min; Zhu, Ai Jun; Huang, Jin Gang; Zhao, Hong Ting; Li, Yong Feng
Abstract: In this study, the feasibility of hydrogen production from food waste using a combined bioprocess of solid-state fermentation (SSF) and dark fermentation was investigated. Food waste was first used to produce glucoamylase and protease enzymes via SSF using Aspergillus awamori and Aspergillus oryzae . The produced enzymes were then used to release glucose and free amino nitrogen (FAN) from the food waste. Both glucose and FAN increased with increasing of food waste mass ratio from 5% to 15% (w/v). However, the glucose yield and starch conversion decreased from 0.434 g glucose/g food waste and 96.2% to 0.307 g glucose/g food waste and 68.1%, respectively, when the food waste mass ratio increased from 5% to 15% (w/v) probably because of the deactivation caused by high temperature or protease. The food waste hydrolysate was then used as the nutrient source for dark fermentative hydrogen production by Biohydrogenbacterium R3. The best hydrogen yield of 52.4 mL H2 /g food waste was achieved at food waste mass ratio of 5% (w/v). The modified Gompertz model could be used to describe the cumulative hydrogen production for the food waste hydrolysate. The results demonstrated a promising combined bioprocess for hydrogen production from food waste. Highlights: A novel combined bioprocess for hydrogen production was developed. Food waste was used in solid-state fermentation to produce enzymes. The resulting enzymes were utilized to hydrolyze food waste. The food waste hydrolysate was used as feedstock for biohydrogen production. The best H2 yield of 52.4 mL H2 /g food waste was achieved.